Microbiological diagnosis and antimicrobial resistance profile of bovine mastitis causing agents in the municipality of Placas, Pará, Brazil - Raimundo Nonato Colares Camargo Junior; Lenoir Loeblein Silva; Igor Felipe da Silva Coimbra; Welligton Conceição da Silva; Cláudio Vieira de Araújo; Hipócrates de Menezes Chalkidis; Simone Vieira Castro (Acta Scientiarum. Animal Sciences, 2023)
The study was carried out in the region of Placas, Pará. Objective: identify the main causing agents of mastitis, as well as evaluating the resistance profile of the isolated agents against antimicrobials. Methods: Ten properties were evaluated, where 161 animals were submitted to the California Mastitis Test (CMT) for the diagnosis of subclinical mastitis, and milk samples were collected from positive animals and led for culture and antibiogram. Results: In total, 31.06% of the animals were positive for CMT. The main agents identified were Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus agalactiae and Streptococcus bovis. The antibiogram indicated resistance to Penicillin, Ceftazidime and Cephalothin. Conclusion: The properties surveyed showed a high rate of subclinical mastitis, regarding antimicrobial resistance, in general, all agents showed high resistance.